Mewujudkan Budaya Literasi melalui Pengoptimalisasian Pojok Baca di SD Negeri 4 Menteng Kota Palangka Raya - Wahyu Nugroho; Laila Rahmawati; Joni Bungai; Simpun (Bulletin of Community Engagement, 2024)
Building a literacy culture is crucial after the Covid-19 pandemic. There was a learning crisis or learning loss during the pandemic. One alternative is to bring children closer to access to books through a reading corner. This research aims to create a culture of literacy through optimizing the reading corner at SD Negeri 4 Menteng, Palangka Raya City. The service method starts from preparing needs, carrying out reading corner decorations and socializing the importance of reading corners, then evaluating reading corners. Evaluation using a questionnaire to students regarding responses to the presence of a reading corner. Based on the evaluation results of the reading corner program, it can be concluded that this initiative has had a significant positive impact in building a literacy culture in the school environment. The reading corner program has not only succeeded in providing easy access to reading materials, but also created an atmosphere that supports the development of reading habits among students. This can be seen from the increasing frequency of reading activities, growing awareness of the importance of reading, and the development of literacy discussions between students.